2017
DOI: 10.1016/j.idh.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist intervention in patients receiving treatment for Chagas disease: An emerging challenge for non-endemic countries

Abstract: Background: Spain has the second highest number of Chagas disease-infected patients among non-endemic countries. However, there is limited knowledge about pharmacist involvement in managing patients with Chagas disease. Method: A retrospective observational study was performed in two periods (before and after intervention) to describe the characteristics of patients with Chagas disease. Pharmacist intervention, based on two pharmacist-visit programs and development of information for patients, was applied to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Some studies, such as BENEFIT, have demonstrated the effectiveness of BZ in decreasing antibody titers. However, it is perceived that the progression of the disease remains unchanged in those patients with already-established cardiac disease compared to that in patients who do not receive treatment during the chronic phase (7,8), and several studies have shown that BZ has a number of side effects causing patients to withdraw from treatment (9,10).…”
mentioning
confidence: 99%
“…Some studies, such as BENEFIT, have demonstrated the effectiveness of BZ in decreasing antibody titers. However, it is perceived that the progression of the disease remains unchanged in those patients with already-established cardiac disease compared to that in patients who do not receive treatment during the chronic phase (7,8), and several studies have shown that BZ has a number of side effects causing patients to withdraw from treatment (9,10).…”
mentioning
confidence: 99%